2015
DOI: 10.1111/1442-1984.12104
|View full text |Cite
|
Sign up to set email alerts
|

Ample germination ability under wide‐ranging environmental conditions in a common understory tropical palm

Abstract: Although palms play an important ecological role in tropical forests, characteristics related to their germinative niche remain largely unknown. We evaluated the seed germination characteristics of Geonoma schottiana, an abundant palm in the understory of different ecosystems of the Atlantic Rain Forest biome and the gallery forests of the Cerrado biome. We conducted experiments under light and dark conditions at Ψ = 0 MPa, and under two low-water-potential conditions and a flooded condition. Seed germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 59 publications
(167 reference statements)
0
14
0
Order By: Relevance
“…2015; Braz et al . 2016). The last situation was observed in the palm species Geonoma schottiana , with germination synchrony increasing when seeds were subjected to low water potentials (Braz et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2015; Braz et al . 2016). The last situation was observed in the palm species Geonoma schottiana , with germination synchrony increasing when seeds were subjected to low water potentials (Braz et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, most water deficit studies have found that decreasing water potentials lead to a decrease in seed germination and an increase in time to germination (Evans & Etherington 1990;Adams 1999;Dürr et al 2015;Braz et al 2016;Fan et al 2020). Seeds of three species occurring in a Brazilian dry forest showed very little or no germination at water potentials below −0.8 MPa (Dantas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of rainfall reductions could be more pronounced in small fragments because it tends to be drier due to edge effects (Laurance et al, 2002). As Braz et al (2016) stated that Geonoma seeds are sensitive to water scarcity, this might explain the lower seedling survival rate. However, in a climate change scenario, Geonoma may not be endangered in small forest fragments, as an increase in precipitation and temperature is predicted for southeastern Brazil over the coming decades (Vale et al, 2021), along with a probable decrease in the duration of dry spells (Nunes et al, 2018).…”
Section: Discussionmentioning
confidence: 99%